Pentacam – the new way for anterior eye segment imaging and mapping - Kopacz, Dorota; Maciejewicz, Piotr; Kęcik, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Accurate preoperative measurements are required for refractive and cataract surgery. Pentacam is a new imaging system for anterior eye segment study. The authors present technique and the range of measurements; topography of both anterior and posterior corneal surface from limbus to limbus, densitometry, anterior chamber angle, volume and depth, lens densitometry and 3D-virtual model of the anterior eye segment are taken. All those structures are shown thanks to rotating Scheimpflug camera, which generates three-dimension images. Any eye movements are detected by a second camera and corrected for, in the process. All results are written down on PC and are available for the prospective studies.